Growth of the surface area of separated liquid fragments during high-temperature fragmentation of an inhomogeneous liquid drop; Technical Physics Letters; Vol. 43, iss. 6 - Piskunov M. V. Maksim Vladimirovich (2017, 2017)
Title screen